1994
DOI: 10.1007/bf01839269
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic activity of intestinal musclein vitro taken from horses with and without equine grass sickness

Abstract: Equine grass sickness (EGS) is a pan-dysautonomia of horses that involves central and peripheral neuronal degeneration and ultimately depletion. This is the first reported functional study on the motility of equine intestine taken immediately post mortem from horses with EGS. Strips of smooth muscle from the small intestine of healthy and EGS-affected horses were suspended in an organ bath and their motility was measured isometrically. The activity of the cholinergic system was studied. Physostigmine enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Some evidence suggests a neurochemical link to amyloid processing and, in particular, a role for cholinergic innervation. It was early recognized that a common characteristic shared by the several neuronal groups demonstrating Alzheimer pathology was the presence of AChE (24,64,173,184). This hypothesis is of particular interest since it links the two current major hypotheses of Alzheimer dysfunction -neuronal acetylcholine loss and amyloid deposition -and provides additional rationale for cholinergic replacement therapy.…”
Section: Actions On Amyloid Protein Processingmentioning
confidence: 97%
See 2 more Smart Citations
“…Some evidence suggests a neurochemical link to amyloid processing and, in particular, a role for cholinergic innervation. It was early recognized that a common characteristic shared by the several neuronal groups demonstrating Alzheimer pathology was the presence of AChE (24,64,173,184). This hypothesis is of particular interest since it links the two current major hypotheses of Alzheimer dysfunction -neuronal acetylcholine loss and amyloid deposition -and provides additional rationale for cholinergic replacement therapy.…”
Section: Actions On Amyloid Protein Processingmentioning
confidence: 97%
“…The effects of physostigmine have been examined experimentally in a variety of memory paradigms, passive, active, and those induced by cholinergic deficits and lesions. These effects have been reviewed (81,184).…”
Section: Effects On Memorymentioning
confidence: 99%
See 1 more Smart Citation
“… 63 There is no explanation for the apparent susceptibility of the ileum, although it has been suggested that the putative neurotoxin might be absorbed preferentially in this region 61 . There is reduced release of acetylcholine in vitro in tissues taken from cases of acute EGS, particularly in ileal preparations 65 and a good correlation between functional cholinergic responses in vitro and enteric neuronal morphology 64…”
Section: Neuropathologymentioning
confidence: 99%
“…[67][68][69][70][71][72] Physostigmine exerts a stereoselective inhibition by acting as a pseudosubstrate and transferring a carbamate residue to the enzyme's active site.…”
Section: Synthesis Of Acetylcholine (Ach)mentioning
confidence: 99%